THE RELATIONSHIP OF PROFITABILITY FACTORS TO PAST AND FUTURE STOCK RETURNS (EMPIRICAL STUDY OF CONVENTIONAL BANK COMPANIES INDEX IDX FINANCE PERIOD 2020-2023) - Chin, Kevin Nicholas; Setiawan, Temy (Jurnal Akuntansi Bisnis, 2024)
Background: This study seeks to explore the connection between profitability and stock returns, specifically investigating how past stock returns influence profitability and how profitability impacts future stock returns. The research focuses on banking companies listed in the IDX Finance index during the 2020-2023 period.Objective: This study aims to offer empirical evidence regarding the impact of past stock returns on profitability and the impact of profitability on future stock returns.Research Methods: This study utilizes a quantitative approach, focusing on a sample of 37 conventional banks that exists on the Indonesia Stock Exchange (IDX) Finance in 2020 – 2023. Data analysis was performed using the PLS-SEM method, with the assistance of SmartPLS 4.0 software.Research Results: The study findings revealed that past stock returns significantly enhance the net interest margin (NIM), which in turn positively influences the return on assets (ROA). Consequently, ROA plays a vital role in driving future stock returns upward.Research Originality/Novelty: This research provides fresh perspectives by examining the connection between profitability and stock returns, both historically and prospectively, within the context of Indonesia's banking sector. Additionally, it highlights the factors that impact stock returns and the profitability of banking institutions.